The Near Infrared Imager and Slitless Spectrograph for the James Webb Space Telescope. IV. Aperture Masking Interferometry. (1st January 2023) - Sivaramakrishnan, Anand; Tuthill, Peter; Lloyd, James P.; Greenbaum, Alexandra Z.; Thatte, Deepashri; Cooper, Rachel A.; Vandal, Thomas; Kammerer, Jens; Sanchez-Bermudez, Joel; Pope, Benjamin J. S.; Blakely, Dori; Albert, Loïc; et al.
Abstract: The James Webb Space Telescope's Near Infrared Imager and Slitless Spectrograph (JWST-NIRISS) flies a 7-hole non-redundant mask (NRM), the first such interferometer in space, operating at 3–5 μ m wavelengths, and a bright limit of ≃4 mag in W2. We describe the NIRISS Aperture Masking Interferometry (AMI) mode to help potential observers understand its underlying principles, present some sample science cases, explain its operational observing strategies, indicate how AMI proposals can be developed with data simulations, and how AMI data can be analyzed. We also present key results from commissioning AMI. Since the allied Kernel Phase Imaging (KPI) technique benefits from AMI operational strategies, we also cover NIRISS KPI methods and analysis techniques, including a new user-friendly KPI pipeline. The NIRISS KPI bright limit is ≃8 W2 (4.6 μ m) magnitudes. AMI NRM and KPI achieve an inner working angle of ∼70 mas, which is well inside the ∼400 mas NIRCam inner working angle for its circular occulter coronagraphs at comparable wavelengths.